(untitled) (Research, Society and Development, 2021)
Childhood sleep-related problems can predict later emotional and behavioral disturbances, such as anxiety. Thus, this study aimed to investigate the relationship between sleepiness and anxiety symptoms throughout the semester in schoolchildren aged 9 to 11 years old. Children enrolled in a public school, located in Vitória de Santo Antão, Pernambuco, Brazil, of both genders, without sleep disorders, physical disabilities or cognitive disorders (n = 88) were evaluated. The State-Trait Anxiety Inventory was used to analyze mood. Subjective sleep assessment was performed using the Epworth Sleepiness Scale and the Horne & Ostberg Morningness and Eveningness Questionnaire (MEQ-HO). The questionnaires were applied in the morning at the beginning (P1) and at the end (P2) of the school semester, with the exception of the MEQ-HO. The correlation between sleepiness and state of anxiety in period 1 (r=0.16; p=0.21) was insufficient, as well as in period 2 (r=0.34; p=0.01). There was a low correlation between sleepiness and anxiety traits in period 1, while the correlation was moderate in period 2 (r=0.48; p<0.001). The correlation between sleepiness and the trait and state of anxiety presented a low to moderate correlation in the positive and negative aspects of anxiety. The data reveal that the evaluated students present abnormal daytime sleepiness at the end of the school semester and such alterations can worsen the anxiety trait in the evaluated children.